EFEKTIFITAS PENERAPAN UNDANG-UNDANG FIDUSIA TERHADAP PERJANJIAN KREDIT DENGAN JAMINAN KENDARAAN BERMOTOR - alip rahman (Fakultas Hukum Universitas Swadaya Gunung Jati, 2015)
ABSTRACTThe presence of a wide range of financial institutions is a form of progress in community economic development, Fiduciary itself is an old term that has been known in the Indonesian language. According to Law No. 42 of 1999 About Fiducia is also called